2013
DOI: 10.1172/jci39920
|View full text |Cite
|
Sign up to set email alerts
|

Acylated and unacylated ghrelin impair skeletal muscle atrophy in mice

Abstract: Cachexia is a wasting syndrome associated with cancer, AIDS, multiple sclerosis, and several other disease states. It is characterized by weight loss, fatigue, loss of appetite, and skeletal muscle atrophy and is associated with poor patient prognosis, making it an important treatment target. Ghrelin is a peptide hormone that stimulates growth hormone (GH) release and positive energy balance through binding to the receptor GHSR-1a. Only acylated ghrelin (AG), but not the unacylated form (UnAG), can bind GHSR-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
203
4
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 125 publications
(235 citation statements)
references
References 68 publications
(105 reference statements)
19
203
4
2
Order By: Relevance
“…Although ghrelin may undeniably inhibit cachexia through the GHS-R1a-mediated anti-inflammatory and orexigenic activities, some evidences prove that both acylated and unacylated ghrelin have a direct anti-atrophic activity in skeletal muscles: unacylated ghrelin, which does not bind GHS-R1a and does not activate the GH/IGF-1 axis, reduces burn-induced skeletal muscle proteolysis and TNF-a up-regulation in rats (Sheriff et al 2012), counteracts muscle atrophy induced by either fasting or denervation, and, as a final point, both acylated and unacylated peptides impairs fasting-induced atrophy in Ghsr null mice (Porporato et al 2013).…”
Section: Therapeutic Applications Of Ghrelinmentioning
confidence: 95%
See 1 more Smart Citation
“…Although ghrelin may undeniably inhibit cachexia through the GHS-R1a-mediated anti-inflammatory and orexigenic activities, some evidences prove that both acylated and unacylated ghrelin have a direct anti-atrophic activity in skeletal muscles: unacylated ghrelin, which does not bind GHS-R1a and does not activate the GH/IGF-1 axis, reduces burn-induced skeletal muscle proteolysis and TNF-a up-regulation in rats (Sheriff et al 2012), counteracts muscle atrophy induced by either fasting or denervation, and, as a final point, both acylated and unacylated peptides impairs fasting-induced atrophy in Ghsr null mice (Porporato et al 2013).…”
Section: Therapeutic Applications Of Ghrelinmentioning
confidence: 95%
“…Since unacylated ghrelin shares with ghrelin common high affinity binding sites in various cell lines, including cells lacking GHS-R1a (Baldanzi et al 2002;Cassoni et al 2001Cassoni et al , 2004Filigheddu et al 2007;Granata et al 2007;Jeffery et al 2002;Muccioli et al 2004), and they share biological activities in vivo, also in Ghsr null mice (Porporato et al 2013), both peptides act in all probability through a common, although yet unidentified, receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Both acytylated and unacytylated ghrelin blocks skeletal muscle atrophy in a growth hormone-independent manner (Porporato 2013). In vitro studies have demonstrated that ghrelin may regulate mesenchymal cell development by stimulating myogenesis (Zhang 2007).…”
Section: How the Intervention Might Workmentioning
confidence: 99%
“…We therefore studied lean rats and a transgenic mouse model of systemic UnAG overproduction (19) to test the hypothesis that UnAG 1) lowers mitochondrial ROS production and inflammation and enhances insulin action in lean rodent muscle and 2) normalizes high-fat diet (HFD)-induced muscle metabolic alterations, whole-body insulin resistance, and hyperglycemia. In addition, effects of UnAG were verified in vitro in myotubes, where we also mechanistically tested the hypothesis that UnAG activities are at least partly mediated by positive modulation of autophagy.…”
mentioning
confidence: 99%